Manufacturing method of electromagnetic pure iron plate for magnetic circuit of railway signal relay

By adjusting the hot rolling and cold rolling process parameters, the problems of small grain size and high coercive force of the electromagnetic pure iron annealed plate are solved, and electromagnetic pure iron plates with large grain size, low coercive force and high magnetic induction strength are obtained, which improves product performance and production efficiency.

CN119965039APending Publication Date: 2025-05-09SHENYANG RAILWAY SIGNAL +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510165481.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The existing electromagnetic pure iron annealing plates have small grain size and high coercive force, which is difficult to meet the requirements of the magnetic circuit of railway signal relays for armature and yoke performance.

Method used

By adjusting the hot rolling final rolling temperature, the hot rolling plate slow cooling start temperature and the cold rolling pressure rate, electromagnetic pure iron plates with large grain size, low coercive force and high magnetic induction strength are obtained.

Benefits of technology

The structure uniformity and performance optimization of electromagnetic pure iron sheets is achieved, which reduces production costs and improves product performance and competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119965039A_ABST
    Figure CN119965039A_ABST
Patent Text Reader

Abstract

A manufacturing method of an electromagnetic pure iron plate for a railway signal relay magnetic circuit relates to the technical field of relay material manufacturing, and comprises the following steps: step 1, smelting and forging: smelting in a vacuum induction furnace to prepare an alloy ingot, heating the alloy ingot in a heating furnace, and then forging into a steel billet; 2, hot rolling is conducted, specifically, the forged steel billet is heated and subjected to hot rolling, and hot-rolled experimental steel is slowly cooled; 3, cold rolling is conducted, specifically, cold rolling treatment is conducted after acid pickling; and 4, magnetic annealing is conducted, specifically, the cold-rolled sheet is subjected to magnetic annealing. By regulating and controlling the hot rolling finishing temperature, the slow cooling starting temperature of the hot rolled plate and the cold rolling reduction rate, an electromagnetic pure iron plate product is obtained, and the method has the advantages of being short in technological process and low in cost while low coercive force and high magnetic induction intensity are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of relay material manufacturing, and in particular to a method for manufacturing an electromagnetic pure iron plate material for a railway signal relay magnetic circuit. Background Art

[0002] When the electromagnetic relay coil is energized, the armature is attracted to the core and drives the contact to move; when the current decreases, the armature falls by gravity and drives the contact to move. Therefore, the electromagnetic relay plays the role of automatic adjustment, safety protection, and circuit conversion in the circuit. Electromagnetic relays play an important role in the operation control, safety assurance and system control of high-speed railways. Due to the high speed of high-speed railways, the armature and yoke are required to drive the contacts to respond quickly to ensure the extremely high requirements for working speed and accuracy. Electromagnetic pure iron is a high-quality steel with an iron content of more than 99.5%. It has the advantages of low coercive force, high saturation magnetic induction intensity and high magnetic permeability, as well as low cost and good processing performance. Therefore, it is widely used in electronic appliances, communications, aerospace and other fields. Due to its low coercive force, electromagnetic pure iron can respond quickly to changes in the external magnetic field. The higher magnetic induction intensity also helps to increase the suction force. It is an ideal material for preparing the armature and yoke of electromagnetic relays.

[0003] China's national standard GB / T 6983-2022 divides electromagnetic pure iron into four grades according to coercivity, coercivity aging value-added, maximum magnetic permeability and magnetic induction intensity, namely DT4 (ordinary), DT4A (advanced), DT4E (special grade) and DT4C (super). Among them, DT4C has the lowest coercivity and the best magnetic properties. The coercivity and magnetic induction intensity of electromagnetic pure iron are tissue-sensitive parameters, and their size is related to chemical composition, internal stress and tissue factors. Among them, tissue factors are the most important factors affecting the performance of electromagnetic pure iron. Microstructures with fine grain size, high defect density, and many inclusions and precipitates usually lead to difficulties in the movement of magnetic domains, thereby deteriorating the coercivity of the material. As the grain size increases, the coercivity shows a downward trend. This is because the increase in grain size strengthens the long-range dipole interaction between grains, which increases the possibility of nucleation of reverse magnetization domains. At the same time, as the grain size increases, the overall area occupied by the grain boundary will be relatively reduced, and the lattice distortion and crystal defects in the grain boundary area will be reduced, resulting in a decrease in internal stress and a decrease in coercive force. The magnetic induction intensity is mainly related to the orientation of the grains in the electromagnetic pure iron annealing structure. <001> / / The higher the proportion of ND grains, the higher the magnetic induction intensity tends to be.

[0004] Production practice and research have shown that adjusting the process parameters such as continuous casting, hot rolling, cold rolling and annealing can effectively regulate the structure and performance of electromagnetic pure iron to meet the performance requirements of relay armature and yoke. Chinese patent CN109097549A discloses a cold rolling process for electromagnetic pure iron straight strips, which uses hot-rolled electromagnetic pure iron discs as raw materials, adopts a three-step cold rolling process with two intermediate vacuum annealings to obtain cold-rolled plates, and obtains key parts for railway signal relays after final magnetic annealing. It should be pointed out that the two intermediate vacuum anneals in this process need to be kept at 600 ° C for 12 hours, which is time-consuming. Multiple cold rolling and a total of 24 hours of intermediate vacuum annealing significantly reduce production efficiency. Moreover, from hot-rolled plates to final products, electromagnetic pure iron needs to undergo three cold rolling and annealing cycles, which is easy to form a recrystallized structure composed of fine, equiaxed grains after the final magnetic annealing, which is not conducive to reducing coercivity. This is because the hot rolling finishing temperature currently used is often low (usually not more than 1000 ℃), and the coiling temperature is also low (usually not more than 750 ℃), which makes it easy to obtain a relatively fine hot rolling structure. <001> / / ND grains also account for a relatively low proportion. Under this condition, the intermediate annealing temperature is as low as 600 °C, which is not conducive to the nucleation and growth of recrystallization after cold rolling, and it is easy to obtain a fine magnetic annealing structure. <001> / / The proportion of ND grains may also be low, affecting the optimization of coercive force and magnetic induction intensity. Summary of the invention

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a method for manufacturing electromagnetic pure iron plate for the magnetic circuit of railway signal relays. By regulating the hot rolling final rolling temperature, the hot rolled plate slow cooling start temperature and the cold rolling reduction rate, an electromagnetic pure iron plate product is obtained. While ensuring low coercive force and high magnetic induction intensity, it has the characteristics of short process flow and low cost.

[0006] In order to achieve the above object, the main technical solutions adopted by the present invention include: A method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit comprises the following steps: Step 1: Smelting and forging: In a vacuum induction furnace, the alloy ingot is smelted and prepared, and the alloy ingot is heated to 1150-1250°C in a heating furnace, kept warm for 1-3 hours, and then forged into a steel billet at 1000-1200°C; Step 2: Hot rolling: The forged steel billet is heated to 1100-1250°C, kept at this temperature for 1-3 hours, and then hot rolled. The final rolling temperature is 1020-1060°C. The experimental steel is air-cooled to 750-850°C and then slowly cooled to below 200°C and then air-cooled to room temperature. Step 3, cold rolling: After pickling, cold rolling is carried out, the final cold rolling thickness is 3.5~5 mm, and the cold rolling reduction rate is not more than 20%; Step 4: Magnetic annealing: The cold-rolled sheet was subjected to magnetic annealing, kept at 900-950 °C for 1-2 h, and then cooled to room temperature to obtain an annealed sheet.

[0007] Furthermore, the thickness of the steel billet prepared in step 1 is 40-50 mm.

[0008] Furthermore, in step 2, the hot rolling is performed through 5 to 7 passes to a thickness of 4 to 6 mm.

[0009] Furthermore, in step 2, the slow cooling rate after hot rolling is 1-10°C / min.

[0010] Furthermore, in step 4, the cold-rolled sheet is placed in an annealing furnace for magnetic annealing, and vacuum annealing is adopted during annealing, or annealing is performed in a non-oxidizing atmosphere.

[0011] The electromagnetic pure iron plate is prepared by the manufacturing method of the electromagnetic pure iron plate, and the components of the electromagnetic pure iron plate are as follows by mass percentage: C ≤0.006%, Si 0~0.08%, Mn 0~0.25%, S ≤0.006%, P ≤0.012%, N≤0.003%, Als 0.5~0.8%, Ti ≤0.005%, Cr ≤0.02%, Ni ≤0.02%, Cu ≤0.02%, and the balance is Fe and unavoidable impurities.

[0012] Furthermore, the thickness of the electromagnetic pure iron plate is 3.5-5 mm.

[0013] Furthermore, the average grain size of the electromagnetic pure iron plate is 120-160 μm.

[0014] Furthermore, the coercive force of the electromagnetic pure iron plate is ≤30A / m.

[0015] Furthermore, the magnetic induction intensity B of the electromagnetic pure iron plate is 5000 ≥1.73 T, hardness ≤195 HV.

[0016] The present invention aims to solve the shortcomings of electromagnetic pure iron annealing plate with small grain size and high coercivity. By adjusting the hot rolling final rolling temperature and the hot rolling plate slow cooling start temperature, a coarser hot rolling structure is obtained. After single-stage cold rolling and magnetic annealing, a product with larger grain size (120-160 μm), lower coercivity (≤30A / m) and higher magnetic induction intensity (B 5000≥1.73 T) of electromagnetic pure iron plate. On the one hand, by increasing the hot rolling final rolling temperature and the hot rolling plate slow cooling start temperature, the hot rolled plate grains can be fully grown, thereby obtaining a coarser hot rolled structure. Due to the small number of grain boundaries, deformation substructures such as deformation bands can be reduced during cold rolling, and the recrystallization nucleation rate during annealing can be reduced, which helps to increase the grain size of the annealed plate. A higher hot rolling final rolling temperature is also conducive to obtaining a more uniform hot rolled structure, which helps to improve the uniformity of the structure of the cold rolled and annealed plates. On the other hand, appropriately reducing the cold rolling reduction rate can reduce the cold rolling storage energy, which is also conducive to increasing the grain size of the annealed plate. The present invention avoids the problems of cumbersome procedures and low production efficiency under the original multiple cold rolling and intermediate annealing processes, and solves the problems of fine structure and high coercivity in the traditional single-stage cold rolling process. This innovative electromagnetic pure iron production method helps to reduce production costs and improve product performance and competitiveness.

[0017] The beneficial effects of the present invention are: (1) The method for manufacturing electromagnetic pure iron plate for railway signal relay magnetic circuit provided by the present invention promotes the full growth of recrystallized grains by increasing the hot rolling final rolling temperature and the hot rolled plate slow cooling start temperature, thereby obtaining a hot rolled structure dominated by coarse recrystallized grains and retaining more <001> / / ND oriented grains lay the foundation for obtaining coarse recrystallized structure after cold rolling and annealing, and for improving the magnetic induction of annealed plates.

[0018] (2) Under the condition of coarse hot rolling structure, the present invention simplifies the multiple cold rolling and intermediate annealing processes into a single-stage cold rolling process, eliminating the intermediate annealing process and greatly simplifying the preparation process. Moreover, the magnetic annealed plate has a lower coercive force and a higher magnetic induction intensity, which can meet the requirements of the railway signal relay magnetic circuit for the armature and yoke performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a schematic flow chart of a method for manufacturing an electromagnetic pure iron plate material for a railway signal relay magnetic circuit. DETAILED DESCRIPTION

[0020] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0021] The present invention provides a method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit, such as Figure 1 As shown, the following steps are included: Step 1. Smelting and forging: In a vacuum induction furnace, an alloy ingot of the above composition is smelted and prepared, the alloy ingot is heated to a temperature range of 1150-1250°C in a heating furnace, kept warm for 1-3 hours, and then forged into a billet at a temperature range of 1000-1200°C, with a billet thickness of 40-50 mm.

[0022] Step 2. Hot rolling: The forged steel billet was heated to a temperature range of 1100-1250 °C and kept at this temperature for 1-3 hours for homogenization. It was then hot rolled to a thickness of 4-6 mm through 5-7 passes, with a final rolling temperature of 1020-1060 °C. The experimental steel was air-cooled to 750-850 °C and then slowly cooled to below 200 °C and then air-cooled to room temperature.

[0023] Step 3. Cold rolling: After using hydrochloric acid to remove the iron oxide scale on the surface of the hot-rolled plate, cold rolling is carried out. The final cold rolling thickness is 3.5~5 mm, and the cold rolling reduction rate is not more than 20%.

[0024] Step 4. Magnetic annealing: The cold-rolled sheet was placed in an annealing furnace for final magnetic annealing. After being kept at 900-950 °C for 1-2 h, it was cooled to room temperature with the furnace to obtain an annealed sheet.

[0025] In the above method, the slow cooling rate after hot rolling is 1~10℃ / min.

[0026] In the above method, the final annealing is performed by vacuum annealing or annealing in a non-oxidizing atmosphere.

[0027] The components of the electromagnetic pure iron plate for relays of the present invention are as follows by mass percentage: C ≤0.006%, Si 0-0.08%, Mn 0-0.25%, S ≤0.006%, P ≤0.012%, N ≤0.003%, Als 0.5-0.8%, Ti ≤0.005%, Cr ≤0.02%, Ni ≤0.02%, Cu ≤0.02%, and the balance is Fe and unavoidable impurities.

[0028] The thickness of the electromagnetic pure iron sheet for the above-mentioned relay is 3.5~5 mm.

[0029] The average grain size of the electromagnetic pure iron plate for the relay is 120-160 μm.

[0030] The coercive force of the electromagnetic pure iron plate for the above relay is ≤30 A / m.

[0031] The magnetic induction intensity B of the electromagnetic pure iron plate used for the above relay 5000 ≥1.73 T.

[0032] The hardness of the electromagnetic pure iron sheet material for the above relay is ≤195 HV.

[0033] Annealed plate grain size and <001> / / The proportion of ND grains is a key factor affecting the coercivity, magnetic induction intensity, hardness and other properties of electromagnetic pure iron annealing sheet. The present invention adopts a higher hot rolling final rolling temperature, a higher slow cooling start temperature and a lower cold rolling reduction rate, which can effectively improve the grain size and <001> / / The proportion of ND grains, thereby obtaining an electromagnetic pure iron plate with lower coercive force and higher magnetic induction intensity. The higher hot rolling final rolling temperature and slow cooling temperature provide longer time for the hot-rolled plate grains, increase the hot-rolled plate grain size, and reduce the number of grain boundaries; under the condition of lower cold rolling reduction rate, the number of structures such as deformation bands in the cold-rolled deformed grains is reduced. As a result, the recrystallization nucleation rate along the grain boundary is reduced, and the recrystallization nucleation rate within the crystal is also reduced, thereby obtaining coarser annealed plate grains and ensuring a lower coercive force level. Compared with the prior art, the present invention adopts a higher hot rolling temperature and a lower cold rolling reduction rate, both of which are beneficial to retaining <001> / / ND grains, and suppress the negative effects on magnetic induction intensity <111> / / ND grains are formed, thus obtaining a higher magnetic induction intensity. In addition, by coordinating the hot rolling final rolling temperature, the hot rolling plate slow cooling temperature and the cold rolling reduction rate, the uniform organization of the annealed plate can be ensured, and the grain size is within the range of 120~160μm, so that its hardness meets the requirements.

[0034] The invention provides a method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit, and the composition thereof is within the scope of the Chinese national standard GB / T 6983-2022. C usually exists in a solid solution state in electromagnetic pure iron, and may precipitate in the form of Fe3C when the C content increases, pinning the magnetic domain movement during the magnetization process to increase the coercive force. In addition, more C will precipitate in the form of Fe3C and the like during the service process of the electromagnetic pure iron at a higher temperature, which will also deteriorate the coercive force, so the mass percentage of C used is ≤0.006%. Electromagnetic pure iron often contains a certain amount of Mn element, and S can be combined with Mn to form MnS particles, thereby hindering grain growth during annealing, and the adverse effect of pinning the magnetic domain movement during the magnetization process, which will deteriorate the coercive force, so the mass percentage of S used is ≤0.006%. Adding an appropriate amount of Mn to electromagnetic pure iron is conducive to coarsening the precipitate MnS, which is conducive to grain growth, thereby reducing the coercive force. However, excessive Mn will reduce the phase transition point of electromagnetic pure iron, which is not conducive to increasing the annealing temperature and may also deteriorate the magnetic properties. Therefore, the mass percentage of Mn used is 0~0.25%. P can be dissolved in electromagnetic pure iron, which will change the binding force and activation energy between Fe atoms, so it has an important influence on the growth of recrystallized grains. An appropriate amount of P can promote grain growth and reduce coercivity. However, an increase in P content will have an adverse effect on the mechanical properties and processing properties of electromagnetic pure iron, so the mass percentage of P used is ≤0.012%. N can form AlN precipitation with Al, which plays a role in pinning grain boundaries, thereby reducing grain size and increasing coercivity. Therefore, the mass percentage of N used is ≤0.003%. Adding Al elements can reduce the magnetocrystalline anisotropy constant and magnetostriction constant of the material, which is beneficial to improving magnetic properties and obtaining lower coercivity. Moreover, increasing the Al content can promote the coarsening of inclusions in steel, reduce the pinning effect of fine inclusions on magnetic domains, and increase the phase transition temperature to increase the magnetic annealing temperature, thereby reducing coercivity. However, too high Al content will have an adverse effect on the mechanical properties and processing properties of electromagnetic pure iron. Moreover, as mentioned above, Al may also form AlN precipitation with N, which is not conducive to coercivity, so the Al mass percentage used is 0.5~0.8%. Ti and Cr are strong carbide-forming elements. When the content is high, they are easy to form carbides, thereby increasing coercivity. Therefore, the Ti mass percentage used is ≤0.005%, and the Cr mass percentage used is ≤0.02%. Ni and Cu elements can also form fine precipitates in electromagnetic pure iron, so the Ni mass percentage used is ≤0.02%, and the Cu mass percentage used is ≤0.02%.

[0035] Example 1 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows in mass percentage: C 0.006%, Si 0.05%, Mn 0.15%, S 0.006%, P 0.012%, N 0.003%, Als 0.5%, Ti 0.005%, Cr 0.01%, Ni 0.02%, Cu 0.02%, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 50 mm thick steel billet at a temperature range of 1000~1200 ° C.

[0036] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 5 passes of hot rolling to a thickness of 5 mm, the final rolling temperature of hot rolling was measured to be 1020 °C. The hot-rolled plate was cooled to 750 °C in air, cooled to 200 °C in a pit furnace at a slow cooling rate of 1 °C / min, and air-cooled to room temperature after being taken out of the furnace.

[0037] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 4 mm and the cold rolling reduction rate is 20%.

[0038] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 920 °C for 1 hour and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0039] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 152 μm, the coercive force was 26 A / m, and the magnetic induction intensity B 5000 It is 1.735 T.

[0040] Example 2 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows by mass percentage: C 0.005%, Si 0.08%, Mn 0.25%, S 0.006%, P 0.010%, N 0.003%, Als 0.8%, Ti 0.005%, Cr 0.02%, Ni 0.02%, Cu 0.02%, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 42 mm thick billet in the temperature range of 1000~1200 ° C.

[0041] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 7 passes of hot rolling to a thickness of 5.8 mm, the final rolling temperature of hot rolling was measured to be 1060 °C. The hot-rolled plate was cooled to 850 °C in air, cooled to 200 °C in a pit furnace at a slow cooling rate of 10 °C / min, and then air-cooled to room temperature after being taken out of the furnace.

[0042] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 5 mm and the cold rolling reduction rate is 13.8%.

[0043] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 950 °C for 1 hour and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0044] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 160 μm, the coercive force was 25 A / m, and the magnetic induction intensity B 5000 It is 1.738 T.

[0045] Example 3 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows in mass percentage: C 0.005%, Si 0.02%, Mn 0.05%, S 0.004%, P 0.010%, N 0.003%, Als 0.63%, Ti 0.004%, Cr 0.01%, Ni 0.01%, Cu 0.01%, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 40 mm thick billet at a temperature range of 1100~1220 ° C.

[0046] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 5 passes of hot rolling to a thickness of 4 mm, the final rolling temperature of hot rolling was measured to be 1025 °C. The hot-rolled plate was cooled to 800 °C in air, cooled to 150 °C in a pit furnace at a slow cooling rate of 5 °C / min, and then air-cooled to room temperature after being taken out of the furnace.

[0047] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 3.5 mm and the cold rolling reduction rate is 12.5%.

[0048] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 900 °C for 1.5 hours and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0049] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 130 μm, the coercive force was 30 A / m, and the magnetic induction intensity B 5000 It is 1.733 T.

[0050] Example 4 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows by mass percentage: C 0.006%, Si 0.05%, Mn 0.15%, S 0.006%, P 0.012%, N 0.003%, Als 0.5%, Ti 0.005%, Cr 0.01%, Ni 0.02%, Cu 0.02%, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 45 mm thick billet at a temperature range of 1000~1200 ° C.

[0051] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 5 passes of hot rolling to a thickness of 6 mm, the final rolling temperature of hot rolling was measured to be 1040 °C. The hot-rolled plate was cooled to 780 °C in air, cooled to 200 °C in a pit furnace at a slow cooling rate of 1 °C / min, and air-cooled to room temperature after being taken out of the furnace.

[0052] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 5 mm and the cold rolling reduction rate is 16.7%.

[0053] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 915°C for 1 hour and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0054] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 148 μm, the coercive force was 27 A / m, and the magnetic induction intensity B 5000It is 1.736 T.

[0055] Example 5 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows in mass percentage: C 0.006%, Si 0.05%, Mn 0.15%, S 0.006%, P 0.012%, N 0.003%, Als 0.7%, Ti 0.005%, Cr 0.01%, Ni 0.02%, Cu 0.02%, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 40 mm thick steel billet in the temperature range of 1000~1200 ° C.

[0056] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 5 passes of hot rolling to a thickness of 4.9 mm, the final rolling temperature of hot rolling was measured to be 1030 °C. The hot-rolled plate was cooled to 770 °C in air, cooled to 200 °C in a pit furnace at a slow cooling rate of 1 °C / min, and air-cooled to room temperature after being taken out of the furnace.

[0057] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 4 mm and the cold rolling reduction rate is 18.4%.

[0058] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 940 °C for 1 hour and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0059] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 132 μm, the coercive force was 29 A / m, and the magnetic induction intensity B 5000 It is 1.730 T.

[0060] Example 6 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows by mass percentage: C 0.006%, Si 0.05%, Mn 0.15%, S 0.006%, P 0.012%, N 0.003%, Als 0.74%, Ti 0.005%, Cr 0.01%, Ni 0.02%, Cu 0.02%, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 50 mm thick billet at a temperature range of 1000~1200 ° C.

[0061] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 5 passes of hot rolling to a thickness of 4.1 mm, the final rolling temperature of hot rolling was measured to be 1045 °C. The hot-rolled plate was cooled to 825 °C in air, cooled to 200 °C in a pit furnace at a slow cooling rate of 1 °C / min, and air-cooled to room temperature after being taken out of the furnace.

[0062] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 3.5 mm and the cold rolling reduction rate is 14.6%.

[0063] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 920 °C for 1 hour and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0064] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 145 μm, the coercive force was 28 A / m, and the magnetic induction intensity B 5000 It is 1.737 T.

[0065] Comparative Example 1 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows in mass percentage: C 0.015%, Si 0.3%, Mn 0.3%, S 0.01%, P0.012%, N 0.003%, Als 0.5%, Ti0.005%, Cr 0.01%, Ni 0.02%, Cu 0.02%, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 50 mm thick billet at a temperature range of 1000~1200 ° C.

[0066] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 5 passes of hot rolling to a thickness of 9 mm, the final rolling temperature of hot rolling was measured to be 1030 °C. The hot-rolled plate was cooled to 700 °C in air, cooled to 200 °C in a pit furnace at a slow cooling rate of 1 °C / min, and then air-cooled to room temperature after being taken out of the furnace.

[0067] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 4 mm and the cold rolling reduction rate is 55.6%.

[0068] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 900 °C for 1 hour and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0069] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample, and the coercive force and magnetic induction intensity were measured. The average grain size was 52 μm, the coercive force was 50 A / m, and the magnetic induction intensity B 5000 It is 1.714 T.

[0070] The components used in this comparative example have high contents of C, Si, S and Mn elements, a low starting temperature of 700°C for slow cooling of the hot rolled sheet, and a high cold rolling reduction rate of 55.6%. Due to the high C content, Fe3C can be precipitated during the annealing of the cold rolled sheet, significantly improving the coercive force. Due to the high content of S and Mn elements, fine MnS is easily formed to hinder the growth of grains, and the low starting temperature for slow cooling of the hot rolled sheet reduces the grain size, increases the number of grain boundaries, increases the magnetization resistance, and thus increases the coercive force. In addition, due to the high cold rolling reduction rate, the unfavorable effects on the magnetic induction intensity are promoted. <111> / / ND grain nucleation makes the annealed plate <001> / / The proportion of ND grains is reduced, resulting in a lower magnetic induction intensity.

[0071] Comparative Example 2 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingot is as follows in mass percentage: C 0.005%, Si 0.08%, Mn 0.1%, S 0.006%, P 0.012%, N 0.003%, Als 0.1%, Ti 0.005%, Cr 0.01, Ni 0.02, Cu 0.02, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 50 mm thick billet at a temperature range of 1000-1200 ° C.

[0072] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 7 passes of hot rolling to a thickness of 6 mm, the final rolling temperature of hot rolling was measured to be 850 °C. The hot-rolled plate was cooled to 800 °C in air, cooled to 200 °C in a pit furnace at a slow cooling rate of 10 °C / min, and then air-cooled to room temperature after being taken out of the furnace.

[0073] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, it is cold rolled to 5 mm, and the cold rolling reduction rate is 16.7%.

[0074] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 930 °C for 1 hour and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0075] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 70 μm, the coercive force was 47 A / m, and the magnetic induction intensity B 5000 It is 1.719 T.

[0076] The comparative example adopts a low Al content and a low hot rolling final rolling temperature of 850°C. Due to the low Al content, the austenite / ferrite phase transition temperature is low, which may cause the steel to fall into the austenite and ferrite two-phase region during annealing at 930°C, resulting in a smaller average grain size and increased coercivity. In addition, due to the low hot rolling final rolling temperature of 850°C, it is easy to obtain a hot rolled structure with incomplete recrystallization and a smaller grain size, which promotes the unfavorable effect on magnetic induction intensity. <111> / / ND grain nucleation makes the annealed plate <001> / / The proportion of ND grains is reduced, resulting in lower magnetic induction intensity.

[0077] Comparative Example 3 Step 1. Smelting and forging: Smelt and prepare alloy ingots in a vacuum induction furnace. The composition of the alloy ingots is as follows by mass percentage: C 0.01%, Si 0.05%, Mn 0.2%, S 0.006%, P 0.01%, N 0.007%, Als 0.92%, Ti0.03%, Cr 0.01, Ni 0.02, Cu 0.02, and the balance is Fe and unavoidable impurities. The alloy ingot is heated to 1200 ° C in a heating furnace, kept warm for 2 hours, and then forged into a 40 mm thick billet at a temperature range of 1100~1220 ° C.

[0078] Step 2. Hot rolling: The steel ingot was heated in a furnace at 1200 °C and kept warm for 2 h. After being taken out, it was rapidly hot rolled at a starting temperature of 1200 °C. After 5 passes of hot rolling to a thickness of 10 mm, the final rolling temperature of hot rolling was measured to be 930 °C. The hot-rolled plate was cooled to 800 °C in air, cooled to 150 °C in a pit furnace at a slow cooling rate of 5 °C / min, and then air-cooled to room temperature after being taken out of the furnace.

[0079] Step 3. Cold rolling: After pickling to remove the iron oxide scale on the surface of the plate, cold rolling is performed. The final cold rolling thickness is 3.5 mm and the cold rolling reduction rate is 65%.

[0080] Step 4. Magnetic annealing: Place the cold-rolled sheet in an annealing furnace in an Ar atmosphere for final annealing. Keep at 900 °C for 1.5 hours and then cool in the furnace to produce an electromagnetic pure iron annealed sheet.

[0081] The obtained electromagnetic pure ferromagnetic annealed plate was made into a metallographic sample. After grinding, mechanical polishing and 4% nitric acid alcohol corrosion, the longitudinal section microstructure was observed using an optical microscope to determine the average grain size. The obtained electromagnetic pure ferromagnetic annealed plate was made into a magnetic detection sample to determine the coercive force and magnetic induction intensity. The average grain size was 82μm, the coercive force was 44 A / m, and the magnetic induction intensity B 5000 It is 1.729 T.

[0082] The components used in this comparative example have high contents of N, Al and Ti elements, a low hot rolling final rolling temperature of 930°C, and a high cold rolling reduction rate of 65%. Due to the high N content, AlN can be precipitated during the annealing process, which refines the grains by pinning the grain boundaries and moving them, significantly improving the coercive force. Due to the high contents of C, N and Ti elements, small precipitates such as TiN and TiC are easily formed to hinder grain growth, reduce the grain size, increase the number of grain boundaries, increase the magnetization resistance, and thus increase the coercive force. In addition, since the hot rolling final rolling temperature is low and the cold rolling reduction rate is high at 65%, a large number of deformation band structures are formed in the cold-rolled sheet, which promotes the unfavorable effects on the magnetic induction intensity. <111> / / ND grain nucleation makes the annealed plate <001> / / The proportion of ND grains is reduced, resulting in a lower magnetic induction intensity.

[0083] In summary, by comparing the embodiments with the comparative examples, it is found that by regulating the hot rolling finish temperature, the hot rolled plate slow cooling start temperature and the cold rolling reduction rate, electromagnetic pure iron magnetic annealed plates with different thicknesses can be obtained based on a single-stage cold rolling process. The plates have the characteristics of coarse structure, low coercive force and high magnetic induction intensity, and avoid the cumbersome process of multiple cold rolling and annealing, which has made a certain contribution to the development of electromagnetic pure iron.

[0084] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. Alterations, modifications, substitutions and variations of the above embodiments by a person skilled in the art are all within the scope of the present invention.

Claims

1. A method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit, characterized in that: The steps include: Step 1: Smelting and forging: In a vacuum induction furnace, the alloy ingot is smelted and prepared, and the alloy ingot is heated to 1150-1250°C in a heating furnace, kept warm for 1-3 hours, and then forged into a steel billet at 1000-1200°C; Step 2: Hot rolling: The forged steel billet is heated to 1100-1250°C, kept at this temperature for 1-3 hours, and then hot rolled. The final rolling temperature is 1020-1060°C. The experimental steel is air-cooled to 750-850°C and then slowly cooled to below 200°C and then air-cooled to room temperature. Step 3, cold rolling: After pickling, cold rolling is carried out, the final cold rolling thickness is 3.5~5 mm, and the cold rolling reduction rate is not more than 20%; Step 4: Magnetic annealing: The cold-rolled sheet was subjected to magnetic annealing, kept at 900-950 °C for 1-2 h, and then cooled to room temperature to obtain an annealed sheet.

2. The method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit according to claim 1, characterized in that: The thickness of the steel billet prepared in step 1 is 40-50 mm.

3. The method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit according to claim 1, characterized in that: In step 2, the hot rolling is performed through 5 to 7 passes to a thickness of 4 to 6 mm.

4. The method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit according to claim 1, characterized in that: The slow cooling rate after hot rolling in step 2 is 1-10°C / min.

5. The method for manufacturing an electromagnetic pure iron plate for a railway signal relay magnetic circuit according to claim 1, characterized in that: In the step 4, the cold-rolled sheet is placed in an annealing furnace for magnetic annealing, and vacuum annealing or annealing in a non-oxidizing atmosphere is adopted during annealing.

6. The electromagnetic pure iron plate prepared by the method for manufacturing the electromagnetic pure iron plate according to any one of claims 1 to 5, characterized in that: The composition of electromagnetic pure iron plate is as follows by mass percentage: C ≤0.006%, Si 0~0.08%, Mn 0~0.25%, S ≤0.006%, P ≤0.012%, N ≤0.003%, Als 0.5~0.8%, Ti ≤0.005%, Cr ≤0.02%, Ni ≤0.02%, Cu ≤0.02%, and the balance is Fe and unavoidable impurities.

7. The electromagnetic pure iron plate according to claim 6, characterized in that: The thickness of the electromagnetic pure iron plate is 3.5-5 mm.

8. The electromagnetic pure iron plate according to claim 6, characterized in that: The average grain size of the electromagnetic pure iron plate is 120-160 μm.

9. The electromagnetic pure iron plate according to claim 6, characterized in that: The coercive force of the electromagnetic pure iron plate is ≤30A / m.

10. The electromagnetic pure iron plate material according to claim 6, characterized in that: The magnetic induction intensity B of the electromagnetic pure iron plate 5000 ≥1.73 T, hardness ≤195 HV.

Citation Information

Patent Citations

  • Method for cold rolling process of electromagnetic pure iron straight strip material

    CN109097549A